Renal outcomes with aliskiren in patients with type 2 diabetes: a prespecified secondary analysis of the ALTITUDE randomised controlled trial. Issue 4 (April 2016) - Heerspink, Hiddo J L; Persson, Frederik; Brenner, Barry M; Chaturvedi, Nish; Brunel, Patrick; McMurray, John J; Desai, Akshay S; Solomon, Scott D; Pfeffer, Marc A; Parving, Hans-Henrik; de Zeeuw, Dick
Summary: Background: The primary results of the ALTITUDE trial showed no benefit of aliskiren on renal outcomes (doubling of serum creatinine and end-stage renal disease) when used as an adjunct to angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) in patients with type 2 diabetes and chronic kidney disease or cardiovascular disease. We did a prespecified analysis of the ALTITUDE trial to analyse the effects of aliskiren on surrogate renal outcomes in all patients and on primary renal outcomes in subgroups of patients. Methods: In the double-blind, randomised, controlled ALTITUDE trial, 8561 patients with type 2 diabetes and chronic kidney disease or cardiovascular disease were randomly assigned (1:1) to receive aliskiren 300 mg per day or placebo as an adjunct to ACE inhibitors or ARBs. Randomisation was stratified on the basis of baseline urinary albumin-to-creatinine ratio and presence of cardiovascular disease history, and treatment assignments were masked to all patients and study staff. Patients were followed up for a median of 2·6 years (IQR 2·0–3·2). In our secondary analysis, we investigated prespecified intermediate renal outcomes of transitions in albuminuria stages (ie, transitions between normoalbuminuria, microalbuminuria, and macroalbuminuria) and rate of change of estimated glomerular filtration rate (eGFR). We investigated all outcomes in the intention-to-treat population. The primary composite renal outcome of ALTITUDE was defined as a sustained doubling of serum creatinine, end-stage renal disease, or renal death. The ALTITUDE trial is registered withClinicalTrials.gov, numberNCT00549757 . Findings: Aliskiren significantly decreased progression (hazard ratio [HR] 0·83, 95% CI 0·75–0·93) and increased regression (HR 1·29, 95% CI 1·19–1·39) of transitions in albuminuria classes. The annual rate of change of eGFR was −3·1 mL/min/1·73 m 2 per year (95% CI −2·9 to −3·3) in the aliskiren group and −3·0 mL/min/1·73 m 2 per year (−2·8 to −3·2) in the placebo group (p=0·52). eGFR change during the first 6 months was significantly larger with aliskiren than with placebo (−2·5 mL/min/1·73 m 2, 95% CI −2·9 to −2·2 vs −1·4 mL/min/1·73 m 2, 95% CI −1·7 to −1·0; p<0·0001). Subsequent eGFR change did not differ significantly between groups (−2·8 mL/min/1·73 m 2 per year, 95% CI −3·0 to −2·6 with aliskiren vs −3·1 mL/min/1·73 m 2 per year, 95% CI −3·3 to −2·8 with placebo; p=0·068). The absence of a benefit of aliskiren on the primary composite renal endpoint in the overall population was also seen in various subgroups. Interpretation: Aliskiren showed no beneficial effect on hard renal outcomes in the overall population or in various subgroups, but delayed progression to microalbuminuria and macroalbuminuria, and improved regression to microalbuminuria and normoalbuminuria. Whether the chosen intermediates are poor surrogates for clinical outcomes or whether off-target effects disrupt the association between the surrogate and clinical outcomes requires further study. Funding: Novartis.